Deconstructing the Legitimacy of Patriarchy through Qur’anic Reinterpretation and Gender Education: Case Study in Bima’s Muslim Society - Mekadina, Nur Arisah; Atika, Sri; Nurbaitillah, Nurbaitillah; Muslimin, Muslimin; Zuhrah, Zuhrah (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2025)
Ideally, the Qur’an as a guide for Muslims contains universal principles of justice and equality that place men and women in balanced relations. However, the reality in the Muslim community of Bima shows that patriarchal structures are legitimized through conservative interpretations of the Qur’an, patrilineal customs, and social norms that position women in subordinate roles. This study aims to analyze how the legitimacy of patriarchy is constructed and maintained through Qur’anic interpretation, local customs, and social structures, as well as to propose deconstruction strategies through the reinterpretation of religious texts and gender education. This article employs a qualitative library research method with descriptive analysis. The findings reveal that the legitimacy of patriarchy in the Muslim community of Bima emerges from the close interaction between customs, conservative interpretations, and patrilineal social systems. Nevertheless, deconstruction can still be achieved through egalitarian reinterpretations of the Qur’an and the strengthening of gender education, thereby opening participatory dialogue between local customs, Islam, and human rights. The synergy of these two approaches provides a significant contribution to weakening patriarchy and offers an alternative model of gender justice within Muslim societies.